The Long-Term Results of ReLEX® SMILE Depending on the Degree of the Corrected Myopia - O. A. Klokova; R. O. Damashauskas; S. V. Kostenev; E. N. Kalaidin (Oftalʹmologiâ, 2020)
The purpose: prospective study of the long-term refractive and visual results of ReLEx® SMILE, depending on the degree of corrected myopia.Material and methods. The three study groups included 71 patients; the mean age was 26.48 ± 5.5 years. Group I consisted of 20 patients (39 eyes) mean SE –2.62 ± 0.87 D, group II — 26 patients (51 eyes), mean SE 4.68 ± 0.74 D, Group III — 25 patients (47 eyes), mean SE 6.88 ± 0.72 D. All patients underwent femtolaser correction of myopia using the ReLEx® SMILE method with the VisuMax™ laser system (Carl Zeiss Meditec AG).Results. Uncorrected visual acuity of 09 — 1.0 was noted in 34 eyes (87.2 %) in group I, in II — in 43 eyes (84.3 %), in 37 eyes (78.7 %) in group III. The efficiency coefficient was 1.0 in groups I — II and 0.89 in group III. There was no decrease in corrected visual acuity (CVA) during the correction of mild and moderate myopia, in group III it was recorded by 0.1 in two cases (4 %), by 0.2 in one case (2 %), the safety factor in I — II groups 1.0, in III 0,89. Two years after ReLEx® SMILE, refraction of ± 0.5 D from planned in the study groups was achieved, respectively, in 94.9, 88.2, 76.6 % of cases, ± 1.0 D in 100 % of cases in I, II groups, in 97 % of cases in III group. The predictability coefficient was 0.95 in group I, 0.88 in group II, and 0.77 in group III. Refractive regression compared with the results 1 month postoperatively was 0.08 D in group I, 0.1 D in group II, and 0.16 D in group III. Analysis of the long-term results of ReLEx® SMILE allows us to conclude: the method is safe and effective, provides high predictability of refractive results in correcting various degrees of myopia. Further study of the long-term results of the operation, the creation and use of nomograms, taking into account the individual characteristics of the cornea, will improve the predictability and stability of refractive results in the correction of high myopia.